2021
DOI: 10.1093/bjsopen/zrab123
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of risk of osteoporosis after gastrectomy for gastric cancer

Abstract: Introduction There are few guidelines for screening of osteoporosis in patients who have undergone gastrectomy. This study aimed to develop and validate a nomogram to predict the risk of osteoporosis after gastrectomy in patients with gastric cancer. Methods Bone densitometry results for 522 patients with gastric cancer and 2088 individuals from a health-promotion centre were compared using propensity score matching to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In addition, studies have been conducted to predict risk factors for osteoporosis. Recently, a nomogram has been developed to predict the risk of osteoporosis after gastrectomy for gastric cancer (21). However, we did not find any cases of severe osteoporosis that were misunderstood as recurrence due to a history of multiple surgeries for gastric cancer recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, studies have been conducted to predict risk factors for osteoporosis. Recently, a nomogram has been developed to predict the risk of osteoporosis after gastrectomy for gastric cancer (21). However, we did not find any cases of severe osteoporosis that were misunderstood as recurrence due to a history of multiple surgeries for gastric cancer recurrence.…”
Section: Discussionmentioning
confidence: 58%
“…One potential explanation for this observation could be the transition from normal BMD (HU > 110) pre-gastrectomy to abnormal BMD (HU ≤ 110) postgastrectomy. [30,[42][43][44][45] This shift underscores the potential impact of gastrectomy on bone health, with studies a significant prevalence of osteoporosis development following gastrectomy. For instance, Park et al observed that within 10 years after gastrectomy, 53.5% of patients developed osteoporosis, [42] while Yoo et al reported a 34.0% prevalence of osteoporosis during a median follow-up of 6.0 years.…”
Section: Discussionmentioning
confidence: 99%
“…[30,[42][43][44][45] This shift underscores the potential impact of gastrectomy on bone health, with studies a significant prevalence of osteoporosis development following gastrectomy. For instance, Park et al observed that within 10 years after gastrectomy, 53.5% of patients developed osteoporosis, [42] while Yoo et al reported a 34.0% prevalence of osteoporosis during a median follow-up of 6.0 years. [44] Total gastrectomy may carry a heightened risk of osteoporosis compared to partial gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Essential bone malignancy starts in the cells of the bones. Tumor cells are bone cells that have shown to be harmful (Park et al 2021; Tang, Han, and Yin 2022) The information in this segment is all about the importance of bone growth. The vast majority of persons who have tumor cells in their bones do not build their bones properly.…”
Section: Introductionmentioning
confidence: 99%
“…They have cancer cells in their bones that have spread from a tumor somewhere else in their bodies. (Park et al 2021) This disorder is known as auxiliary or metastatic bone disease.Finally, we discuss future research to improve accuracy using the ANN model. In my opinion the above most cited article is best compared to the other articles.…”
Section: Introductionmentioning
confidence: 99%